Perceptions of and attitudes toward the issue of ethical behavior in academic work in higher education and factors contributing to it: a review of studies - Chen, Lin; Saharuddin, Norzihani; Muhamad, Mohd Mokhtar (Uzhhorod National University, 2024)
Relevance. Today, the topic of academic integrity is quite relevant among the scientific and educational communities, and it is based on the fact that ethical behavior in academic work in higher educational institutions is an effective tool that ensures the quality of higher education from the point of view of international standards. The issue of academic cheating in higher education institutions has become globalized, which has forced researchers to focus on the study of academic ethics from different perspectives. Purpose. The main purpose of this study is to investigate the perception and attitude of teachers and students toward the issue of ethical behavior in academic work, as well as factors that contribute to solving the problem of plagiarism. Methodology. The following scientific methods were used during the research: structural-functional method, method of synthesis, logical and comparative analysis, and method of generalization. Results. The study showed that students' attitudes toward the issue of ethical behavior in academic work are similar due to various institutional, socio-cultural, and personal factors, as well as the fact that some individuals have no idea about plagiarism. It has been shown that a number of factors can lead to a problem of ethical behavior in academic work, and no taxonomy can explain either all these factors, how they affect the problem, or how it manifests itself. The study shows that students do not feel guilty for missing classes and using other people's work on their own. Most people demand a tolerant attitude towards plagiarism and accept the practice of passing off other people's tasks and Internet sources as their own. Conclusions. The practical significance of the work is that all theoretical provisions, conclusions, and recommendations can be used in educational institutions by teachers and students to increase their level of knowledge about ethical behavior in academic work.